A comparative study of anticoagulant control in patients on long-term warfarin using home and hospital monitoring of the international normalised ratio. Issue 4 (3rd August 2007) - Bradbury, M J E; Taylor, G; Short, P; Williams, M D
Abstract : Background: Capillary whole-blood point-of-care prothrombin-INR (PT-INR) testing at home is an alternative to hospital-based monitoring for patients on lifelong warfarin. Aim: To retrospectively assess the safety and efficacy of home point-of-care testing for children on long-term warfarin. Method: All patients who had been on point-of-care home monitoring for at least 6 months were included in the study. Their warfarin control was assessed while on home monitoring and compared to that achieved in a similar period before changing from hospital monitoring. Results: Thirty-seven patients were studied for a mean of 1.0 year on clinic monitoring and 1.07 years on home monitoring. The clinic monitoring tests were within a therapeutic range for a median 70.0 (inter-quartile range 34.5) and the home monitoring were within range for median 75.0 (inter-quartile range 44.5). There were no major haemorrhagic or thrombotic complications in either group during the study period. Only 2.3% of all tests had an INR greater than 6.0 with no statistical differences seen between the clinic and home monitoring groups. Conclusion: Home point-of-care testing in children on lifelong warfarin is safe, effective and offers a number of advantages to the child and family. Ongoing training and support for the families is essential for this service.